Teacher support and secondary school students’ learning engagement: A moderated mediation model - Yanhong Shao; Yongna Feng; Xi Zhao; Gang Liu; Lili Zhang (Scientific Reports)
Abstract Learning engagement has attracted increasing interest in recent years, with teacher support, academic self-efficacy, psychological resilience, and positive academic emotion identified as key factors. However, the moderated mediating mechanisms between teacher support and learning engagement remain unexplored. This study aimed to investigate the roles of academic self-efficacy and psychological resilience as mediators, and positive academic emotion as a moderator, in the relationship between teacher support and secondary school students’ learning engagement, from the perspective of the Self-determination Theory and Emotion Regulation Theory. The study involved 665 participants (M age = 14 years, SD = 0.790) randomly selected from four public secondary schools in Eastern China. Data were analyzed with the structural equation model (SEM) in SPSS 24.0, AMOS 24.0, and PROCESS 3.5. Results indicated that teacher support was directly and positively associated with learning engagement. The results also indicated that teacher support was indirectly and positively related to learning engagement through academic self-efficacy and psychological resilience. Additionally, the moderation role of positive academic emotion manifests in the association between academic self-efficacy and psychological resilience. These findings illuminate the complex dynamics underlying learning engagement and provide valuable insights for educators and researchers in promoting optimal learning experiences for secondary school students.